An insider's guide to working for the federal government navigating all levels of government as a civil servant or contractor - Lindner, Dan, 1955- (Bernan Press, 2020)
With simple, to-the-point, explanations of the different branches and agencies of government, insider Dan Lindner guides prospective employees and contractors through the halls of bureaucracy, giving readers everything they need to know to excel in the federal environment.